Gaya Hidup Seksual “Ayam Kampus” dan Dampaknya Terhadap Risiko Penularan Infeksi Menular Seksual (IMS) - Islahul Fikriyah; Husni Abdul Gani; Dewi Rokhmah (Pustaka Kesehatan, 2013)
"Campus Chicken" is a high-risk group for the transmission of STIs. Their sexual lifestyle who often have multiple sexual partners, serving many customers, and do not use condoms when serving customers make the risk of transmission of sexually transmitted infections (STIs) is very large. This study aims to analyze sexual lifestyle “campus chicken” and  its impact on the risk of transmission of sexually transmitted infections (STIs). The research design is a qualitative study. Sampling techniques used snowball sampling, obtained four informants. Collecting data used by in-depth interview. Triangulation method was interview to friends dan taxi driver who became an intermediary “campus chicken”. Analyzing method using thematic analysis. Base on the result of research, most of the informant  to be “campus chicken” because economic factors. All informants have been pregnant and had an abortion. Majority of informants do an abortions in the massage healer. All informants serve clients 3 times in a week. All the informant always do vaginal sex and do not have special sexual technique, choose a rich client, and always have a sex in hotel. Most of the informants did not practice safe sex, they are not consistent in the use of condoms. The risk of transmission of STIs is very large, all the informants had experienced symptoms of STIs. Majority of informants are drinking antibiotics and herbal medicine to treat the symptoms of STIs.Keywords: “Campus Chicken”, Sexual Lifestyle, STIs.